Advanced Traffic Light Controller using FPGA and ARDUINO - Narula, Mandeep Singh; Ayush, Amulya; Kumar, Madhav (Journal of ISMAC, 2024)
This study presents a novel approach to develop a traffic light controller using FPGA and Arduino platforms. The objective is to design a robust, adaptable, and efficient traffic management system. Methodology involves hardware integration of FPGA for real-time processing and Arduino for interfacing with sensors and actuators. The proposed system utilizes FPGA’s parallel processing capabilities for rapid decision-making and Arduino’s flexibility for sensor data acquisition and actuator control. Performance evaluation includes simulation and real-world testing to assess reliability, response time, and scalability. Results demonstrate the effectiveness of the proposed controller in optimizing traffic flow and improving intersection safety.